Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2174/0929867324666171116123345
|View full text |Cite
|
Sign up to set email alerts
|

G4-Interacting DNA Helicases and Polymerases: Potential Therapeutic Targets

Abstract: Guanine-rich DNA can fold into highly stable non-canonical four-stranded DNA structures called G-quadruplexes. These structures present obstacles for the DNA replication machinery, and it has been hypothesized that both eukaryotic DNA helicases and polymerases have evolved to resolve G4 DNA in vivo. Since the discovery of G-quadruplex DNA in the early 1960's, a number of studies have emerged reporting G-quadruplex DNA unfolding by helicase enzymes and DNA synthesis past G4 by specialized translesion polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 136 publications
(138 reference statements)
0
35
0
1
Order By: Relevance
“…[11][12][13][14][15][16] Additionally, due to their stability, G4 structures can challenge DNA replication and must be unfolded by proteins (eg, helicases). [17][18][19] In the absence of regulating proteins, the replication fork stalls at G4 motifs, leading to deletions or mutations. [20][21][22][23][24] Whereas the precise replication of G4 motifs is essential, it is not clear how the replication machinery recognizes these obstacles and how and why replication sometimes stalls approaching G4 motifs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16] Additionally, due to their stability, G4 structures can challenge DNA replication and must be unfolded by proteins (eg, helicases). [17][18][19] In the absence of regulating proteins, the replication fork stalls at G4 motifs, leading to deletions or mutations. [20][21][22][23][24] Whereas the precise replication of G4 motifs is essential, it is not clear how the replication machinery recognizes these obstacles and how and why replication sometimes stalls approaching G4 motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of topology, G4 structures were demonstrated to act as regulatory elements during transcription or telomere maintenance 11‐16 . Additionally, due to their stability, G4 structures can challenge DNA replication and must be unfolded by proteins (eg, helicases) 17‐19 . In the absence of regulating proteins, the replication fork stalls at G4 motifs, leading to deletions or mutations 20‐24 .…”
Section: Introductionmentioning
confidence: 99%
“…During BER, G4 structure formation has been suggested to be stimulated by ROS-mediated oxidation of DNA and APE1 binding, which results in changes in transcription 33 , 34 . In eukaryotes, the polymerases Rev1, η , κ, and θ are involved in the replication of G4 motifs during TLS (reviewed in 66 ). The helicases XPB and XPD of the NER pathway have been shown to act at G4 sites by ChIP-seq 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Although beyond the scope of this review, biological and molecular evidence suggest that certain DNA helicases preserve genomic stability and maintain cellular homeostasis by resolving such alternate DNA structures. G4-resolving helicases are discussed in recent reviews [78,79]. A seminal study from the Lansdorp laboratory first suggested that a putative DNA helicase known as DOG-1 in C. elegans suppressed the accumulation of G4 structures in the lagging strand ssDNA template thereby preventing deletions in regions of the genome characterized by guanine-rich DNA [80].…”
Section: Helicases Resolve Unconventional Dna Structuresmentioning
confidence: 99%